Company Taxation in the European Union - Wawrzyniak, Dorota (Comparative Economic Research. Central and Eastern Europe, 2012)
This paper investigates different measures of corporate tax burden ranging from the most basic ones such as the statutory tax rate to the effective tax rates. Each of these measures has advantages and disadvantages and they may lead to different rankings of countries. One of the reasons lies the fact that they measure different things. The comparison of the statutory tax rates to the effective ones for the EU-27 during the period of 1998-2009 sometimes reveals very significant differences between these indicators. Taking this into consideration, the paper suggests that corporate tax burden analysis should not be limited to the most basic and readily available measure in the form of the statutory tax rate. Different measures are tailored to answer different research questions. Moreover, the article presents changes of company taxation for the EU-27 within 1998-2009.